SPEECH-TO-TEXT TECHNOLOGY AS A TOOL FOR PRONUNCIATION ASSESSMENT AND SELF-CORRECTION IN EFL CONTEXTS: A PILOT STUDY - Henry, James (Elite : English and Literature Journal, 2025)
This pilot study investigates the efficacy of speech-to-text (STT) technology as an objective feedback mechanism for pronunciation assessment and self-correction in English as a Foreign Language (EFL) classroom. The research involved 75 Japanese university students across three classes engaging with STT applications for two 25-minute sessions in a single semester. Data collected included successful transcription rates, specific pronunciation feature improvements, and student affective responses. Results indicate that STT software provides immediate, objective feedback that complements traditional pronunciation instruction methods, with students demonstrating measurable improvement in transcription success rates (from 38% to 62%) and reporting increased confidence in their speaking abilities. This pilot study contributes to the growing field of Computer-Assisted Language Learning (CALL) by offering a practical, accessible approach to pronunciation feedback that can be implemented with minimal technological requirements and time investment